Aromadendrin-4’-O-β-D-glucopyranosyl (1→6)-O-β-D-xylo-pyranoside, A New Dihydroflavonolglycoside from the Aerial Part of Dalbergia Iatifolia Roxb. - Yadava, R.N.; Roy, Anila; Jain, Neeru (Asian Journal of Chemistry, 2010)
The isolation and structural elucidation of a new dihydroflavonol glycoside, aromadendrin-4' -O-β-D-glucopyranosyl (1→6)-O-β-D-xylopyranoside is reported.